Integrative Priming of Compositional and Locative Relations - Jones, Lara L.; Wurm, Lee H.; Calcaterra, Ryan D.; Ofen, Noa (Frontiers in Psychology, 2017)
Integrative priming refers to the facilitated recognition of a target word (bench) as a real word following a prime (park). Prior integrative priming studies have used a wide variety of integrative relations including temporal (summer rain), topical (travel book), locative (forest river), and compositional (peach pie) relations. Yet differences in the types of integrative relations may yield differences in the underlying explanatory processes of integrative priming. In this study, we compared the magnitude, time course, and three theoretically based correlates of integrative priming for compositional (stone table) and locative (patio table) pairs in a lexical decision task across four stimulus onset asynchronies (SOAs; 50, 300, 800, and 1600 ms). Based on the Complementary Role Activation theory, integrative ratings (the extent to which the prime and target can be combined into a meaningful phrase) were predicted to facilitate target RTs. Based on the Embodied Conceptual Combination (ECCo) theory, the local co-occurrence of the prime and target, and the ability to perceptually simulate (visually experience) the prime-target pair were tested as predictors. In comparison to unrelated pairs (nose table), target RTs were faster for the compositional and locative pairs, though did not differ between these relations. In support of the Complementary Role Activation theory, integrative ratings predicted target RTs above and beyond our control variables. In support of the ECCo theory, co-occurrence emerged as an early predictor of target RTs, and visual experience ratings was a reliable predictor at the 300 ms SOA, though only for the compositional relations.